The crimes of wildlife trafficking issues of justice, legality and morality - Sollund, Ragnhild Aslaug 1959- (Routledge, 2019)
This book examines trade and trafficking in endangered animal species and how the trade increasingly puts large numbers of nonhuman species at risk. Focusing on illegal trafficking, the book also discusses the harmful aspects of the trade and trafficking which is taking place in concordance with laws and regulations. Drawing on the findings of empirical research from Norway and Colombia, the study discusses how this global, transnational trend is addressed, and features of the trade and the ways in which it is controlled in the two case study locations. It also explores the motives driving the trade, and the consequences in terms of animal abuse and environmental harm. The book discusses whether internationally agreed measures, such as international conventions, actually help prevent the trade. Possible ways to address the harms of wildlife trade are considered, including a total ban. The work draws on a green criminology and eco feminist theoretical framework to provide a broad perspective on concepts such as harm, animal rights, species justice and speciesism
Description based on online resource; title from digital title page (viewed on March 06, 2019)
Keywords: Wildlife crimes; Wildlife smuggling; Wild animal trade / Moral and ethical aspects; Wild animal trade / Law and legislation